The Unseen Strains: An Investigation into the Hidden Cross Links of Household Food Insecurity Access Severity and Unveiling its Role as a Breast Cancer Risk among the Pathan Women - Ghaffar, Fazia (Indus Journal of Bioscience Research, 2024)
Background: In Pakistan, 1 in 8 women is diagnosed with breast cancer, with many facing food insecurity that affects their risk, recurrence, and treatment. This study assesses household food insecurity among newly diagnosed Pathan breast cancer patients and its potential role as a risk factor. Objectives: The study aimed to find an association between breast cancer risk and household food insecurity access (HFIA) screening. The specific objectives were to (1) determine the prevalence HFIA among the newly diagnosed breast cancer patients. (2) quantify the indicators of Household food insecurity Access among the sample. (3) to assess the dietary intake patterns of the patients and the predictability of HFIA scores as predictors of breast cancer risk. Methodology: The current retrospective analytical cross-sectional study consisted of a consent-based consecutive random sample of 125 newly diagnosed breast cancer women patients who were investigated for their household food insecurity access through a standardized scale, and their food intake patterns were determined through a semi-quantitative food frequency questionnaire based on 11 food groups and 176 indigenous food items. Results: The current study found a surprising 100% of the respondents replying “Yes” on for all the scale items though variations in the frequency were there. The household food insecurity access-related “conditions” indicated that 31.2% of the households “ran out of food” during the recall period. In household food insecurity access-related “domains,” 72% of the households experienced many specific domains on the scale. The mean household insecurity access scale score was found to be 18.37 ± 9.13, and the Average HFIAS Score was 3.94 ± 23.04, indicating a gross moderate to severe food insecurity among the study population. The categorical distribution of the households on the scale showed many families were affirmative in the “sometimes” and “often” categories. The percent distribution showed 30.5% families mildly insecure, 41.8% moderately food insecure, 15.7% severely food insecure, and only 12% in the food secure category. The dietary intake patterns showed that many nutrient-dense foods were rarely consumed, while the consumption of seasonal vegetables and cereals was weekly. Wheat, sugars, and ghee were reported to be highly consumed food items. The socio-demographic characteristics such as age, education, total family income, and family size have shown to be the strongest predictors of household food insecurity access. Conclusion: This study reveals widespread food insecurity among Pakistani breast cancer patients, exacerbated by illiteracy, poverty, and malnutrition. Broader research and targeted strategies are needed to address this issue.